Study of inflammatory markers for COVID-19 in control population and in pregnant women: a systematic review - Ahuja, Mayuri; Srivastava, Ruchi; Agarwal, Shelly; Tyagi, Bhumesh; Goel, Neerja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
COVID-19 infection is an inflammatory state and has varied presentation ranging from mild to severe condition. The second wave of COVID-19 resulted in greater mortality and morbidity as compared to first wave both in general as well as in pregnant patient. As the progression of disease is rapid and fatal hence there is a need of reviewing relevant inflammatory markers for predicting the disease course and severity. The inflammatory markers considered are Interleukins, CRP, LDH, serum Ferritin, Neutrophil/ lymphocyte ratio and in some cases serum Procalcitonin. These markers are raised in other inflammatory conditions also and therefore the maximum predictability of various markers differs in different conditions. COVID-19 in pregnancy in itself is challenging as it alters the immunity and hemodynamic and therefore the value of these markers in pregnancy can affect the sensitivity and specificity in predicting the severity of the disease. This review will evaluate the role of inflammatory markers in general population as well as pregnancy with regards to their prognostication in assessing the disease severity.